1999
DOI: 10.1159/000026366
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neuroendocrine Hormones to Promote Reconstitution after Bone Marrow Transplantation

Abstract: A survey of the previous literature and the data shown here indicate that neuroendocrine hormones such as growth hormone and prolactin may be of potential clinical use after bone marrow transplantation (BMT) to promote hematopoietic and immune recovery. The amounts of hormones used in our model do not promote weight gain suggesting that their lymphohematopoietic actions were independent of their anabolic effects. While the hormones may not produce the same extent of immune/hematopoietic effects when compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
(99 reference statements)
0
22
0
1
Order By: Relevance
“…Subsequently, this group [4] demonstrated that rhGH accelerated hematopoietic recovery after syngeneic BM transplantation (BMT). Shortly thereafter, this group [5] reviewed their previous studies and concluded that treatment with GH or PRL, although less potent than agents such as IL-2 or G-CSF, demonstrated real promise in accelerating recovery after BMT. More recent studies [5] have examined the effects of PRL in more detail and confirmed its effectiveness in accelerating recovery after congenic or syngeneic BMT.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…Subsequently, this group [4] demonstrated that rhGH accelerated hematopoietic recovery after syngeneic BM transplantation (BMT). Shortly thereafter, this group [5] reviewed their previous studies and concluded that treatment with GH or PRL, although less potent than agents such as IL-2 or G-CSF, demonstrated real promise in accelerating recovery after BMT. More recent studies [5] have examined the effects of PRL in more detail and confirmed its effectiveness in accelerating recovery after congenic or syngeneic BMT.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…Recombinant human prolactin was endotoxinfree and supplied as a gift by Dr. William J. Murphy, NCI-FCRDC, Frederick, MD, which has been used in their studies [22][23][24][25]. The IL-2-dependent NK cell line NK-92, established from a patient with rapidly progressive non-Hodgkin's lymophoma [26], was purchased from ATCC and maintained in a-MEM (Hyclone) medium containing100U/ml IL-2 and other necessary components as described [26].…”
Section: Cell Culture and Proliferation Assaymentioning
confidence: 99%
“…PRL also increased the proliferating response and cytotoxicity of human, murine or rat NK cells to sensitive or insensitive tumor independently or synergistically with IL-2 in vitro [17][18][19][20]. We previously reported that PRL improved the hematopoiesis and lymphocyte development in syngeneic bone marrow transplantation [21][22][23][24], and exerted anti-tumor effects on tumor-bearing mice in vivo [25]. However, thus far there has been little evidence indicating that PRL can directly affect NK cell function through prolactin receptor on human NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interleukin (IL)-2 has also been given to patients post HSCT to increase immune reconstitution and reduce the relapse rate, but there are conflicting results from different studies. 1 Systemic administration of cytokines is associated with significant toxic effects. 4 Several neuroendocrine hormones, including growth hormone (GH), insulin-like growth factor-1 (IGF-1) and thyroid hormone (triiodothyronine, T 3 ), have been demonstrated to exert stimulatory effects on the immune system.…”
mentioning
confidence: 99%
“…4 The hematopoietic activity of GH and prolactin (PRL) has been studied both in vivo and in vitro. 1 Studies in animal models have shown that these two neuroendocrine hormones are important for hematological activity, but since the models analyzed are deficient in several hormones, the importance of each hormone can not be fully determined. 5,6 GH has been suggested to have an immunomodulatory effect on development, maintenance and function of the immune system.…”
mentioning
confidence: 99%